Analysis of the factors of expansion of spending on pensions in the regime of Invalidity, Old Age and Death of the Costa Rican Cover of Social Security - Sandoval Vásquez, José Fulvio (2019)
This article analyzes, from a macroeconomic point of view, the options that Costa Rica has to control the growth of pension spending in relation to the Gross Domestic Product (GDP), in the case of the regime of invalidity, old-age and deathpensions administered by the Costa Rican Social Security Fund (CCSS). To this end, an econometric model is developed that decomposes the ratio of pension expenditure to GDP into four factors (demography, labor market, eligibility and generosity). The estimation of the model provides the elasticity coefficients of each factor with respect to the ratio of pension expenditure to GDP, which allow analyzing the importance of each element and establishing policy options for the containment of expenditure in order to ensure the sustainability of the RIVM by expense side.